The political economy of poverty and social transformations of the global south - Mariano, Feliz editor; Rosenberg, Aaron L. editor (CROP international poverty studies, 2017)
This book brings forth debates on the production and eradication of poverty from experiences in the global South. It collects a set of innovative articles concentrating on the way in which poverty, as a social process, has been tackled by popular movements and the governments of various states across the globe. Providing new insights into the limitations of traditional strategies to confront poverty, it highlights how social organizations are working to transform the livelihoods of people through bottom-up struggle and more participatory approaches rather than passively waiting for top-down solutions.